Hubungan antara Akhlak dengan Solusi Atas Penyakit Dalam Konteks Pesan Dakwah - Ahmad Hayyan Najikh (An-Nashiha: Journal of Broadcasting and Islamic Comunication Studies, 2022)
The website www.akhlakmuliacenter.com is a website that contains the main studies on good behavior guidance in all aspects of life. On the site there is an explanation regarding the relationship between a disease and our actions (morals). This means that anything that befalls us be it illness, calamity and things that don't please us, it could be a warning from Allah SWT for our mistakes or actions. As in the Al-Qur'an Surah Asy-Syuraa: 30. It is interesting that the da'wah message displayed on the website www.akhlakmuliacenter.com is interesting. Associating behavior (morals) with a person's illness. Therefore, here we will try to examine how the contents of the da'wah messages displayed on the website are seen from the thematic, schematic, semantic and so on structures according to Teun A. Van Dijk's approach. As a result of the use of the method and analysis applied, a conclusion is obtained that the materials used as themes are not much different from the general ones. It's just different in terms of packaging. Besides that, there are also the main values ​​of Islamic religious teachings which are the main material of da'wah such as faith, sharia and morals. There is a need for continuity research from what has been studied. For example, with research on other titles besides the titles that have been researched here, namely "The Beginning of Disease according to the Qur'an" and "Noble Morals-A Solution to Curing Diseases Islamically." It can be with another title or studied with other methods or techniques. Thus it will enrich the material or messages of da'wah that have been studied from various points of view.